Determinants of Regional Fiscal Independence of Local Governments in Ciayumajakuning: A Panel Data Analysis of Local Tax, GRDP, Transparency, and Intergovernmental Transfers - Rifki Fata Ladid; Gugus Irianto; Putu Prima Wulandari (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Regional fiscal independence in the Ciayumajakuning region remained critically low, as local governments continued to rely heavily on intergovernmental transfers rather than locally generated revenue, severely constraining their capacity for autonomous regional development. Objective: This study aimed to determine the effects of local tax revenue, Gross Regional Domestic Product (GRDP), transparency and accountability, and intergovernmental transfers on regional fiscal independence. Methods: This study employed a quantitative approach using panel data regression based on secondary data obtained from regional financial statements and government statistics. Results: Local tax revenue and GRDP had positive and significant effects on fiscal independence, while intergovernmental transfers had a negative and significant effect. Transparency and accountability had no statistically significant effect on fiscal independence. Conclusion: Strengthening regional fiscal autonomy requires a more balanced composition of local revenue sources and reduced dependence on transfer funds, supported by the substantive implementation of governance practices to improve local government performance.